Hyzje.pdf


Aperçu du fichier PDF hyzje.pdf

Page 1 2 3 4 5 6 7 8 9 10 11



Aperçu texte


D’où :
𝜋
1 + cos ( 3)
𝜋
cos ² ( ) =
6
2
1
1+2 3
𝜋
⇒ cos ² ( ) =
=
6
2
4
𝜋
√3
⇒ cos ( ) =
6
2
𝜋

Car d’après le cercle trigonométrique, cos ( 6 ) > 0.
D’où :
𝜋
𝜋
1
sin ( ) = √1 − cos ² ( ) =
6
6
2
De même :

𝜋
1 + cos ( )
𝜋
6
cos ² ( ) =
12
2
√3
1+ 2
𝜋
⇒ cos ² ( ) =
12
2
⇒ cos ² (

𝜋
2 + √3
)=
12
4

√2 + √3
𝜋
)=
12
2

⇒ cos (

𝜋

Car d’après le cercle trigonométrique cos 12 > 0
Et donc :
sin (

𝜋
𝜋
) = √1 − cos ² ( )
12
12

⇒ sin (

𝜋
2 + √3
) = √1 −
12
4